SEAKEEPING BEHAVIOR OF HEXAGONAL CATAMARAN HULL FORM AS AN ALTERNATIVE GEOMETRY DESIGN OF FLAT-SIDED HULL VESSEL - Windyandari, Aulia; Sugeng, Sunarso; Sulaiman, Sulaiman; Ridwan, Mohd.; Yusim, Adi Kurniawan (Journal of Applied Engineering Science, 2023)
The Flat-sided Hull Vessel was introduced to simplify and create an efficient ship production process by eliminating the fairing work, bending, and curved panel line assembly. The built process simplification is expected that the FSHV can be produced by the traditional boat yard. However, the flat hull concept has slightly increased resistance performance. Therefore, implementing a resistance reduction device is endorsed to improve the boat's performance. The focus of the research is to identify the influence of the flat hull concept on seakeeping behavior. The hexagonal catamaran hull form was developed on the deadrise angle, angle of attack, and stern angle variation. Furthermore, the response amplitude operator and the motion spectral density of heave, roll, and pitch motion were calculated. Otherwise, the seakeeping performance of the hexagonal catamaran is compared to the original rounded catamaran. The results show that the hexagonal catamaran hulls have better seakeeping performance in the Beam Sea. However, the conventional catamaran has demonstrated superiority over the hexagonal catamaran in the Bow Quartering and Head Sea conditions.
Keywords: hexagonal catamaran, seakeeping performance, deadrise angle, angle of attack, stern angle